Newer Therapeutic Approaches in Major Depressive Disorder - Jaspreet Kaur; Deepika Puri; Karan Sachdeva; Prithpal S Matreja (International Journal of Human and Health Sciences (IJHHS), 2026)
Major depressive disorder (MDD) is a common health disorders characterized by anhedonia along with physical changes. MDD is a leading cause of disability worldwide. MDD treatment mainly focuses on improving the quality of life of the patients suffering from this disorder. Various modalities of treatment include initiating pharmacotherapy, focussed psychotherapy, or electroconvulsive therapies. The current treatment modalities focus on the monoamine hypothesis with a wide range of drugs available from tricyclic antidepressants (TCAs) to selective serotonin reuptake inhibitors (SSRIs). Despite therapy with the currently available drugs a substantial proportion of patients do not achieve full remission with full-dose titration and there is still persistence of treatment-resistant depression (TRD). The currently available antidepressants drugs are associated with frequent adverse effects with tolerance limiting their long-term adherence. Delivery of psychotherapy has its own set of limitation and one of them is in form of delivery of psychotherapy. As many patients despite optimal therapy of currently available antidepressant drugs one-third of the patients do not respond to the currently available forms of therapy. The understanding of the pathophysiology has increased our knowledge with role of neuroplasticity, disrupted signalling pathway, decreased neurotropic factor expressions and altered functional connectivity of neurocircuitry also playing its role apart from the neurotransmission theory of depression. Opening up avenues for treatment of currently unanswered area for depression which include lag in onset of effect, tolerance to therapy, treatment resistant depression and delay in achieving remission. The current review tries to highlight the various options for treatment of depression for effective treatment of depression. International Journal of Human and Health Sciences Vol. 10 No. 04 Oct’26 Page: 217-226